2008
DOI: 10.1063/1.2890431
|View full text |Cite
|
Sign up to set email alerts
|

Measurement of the specific heat capacity of water-based Al2O3 nanofluid

Abstract: In this letter, we have presented an experimental investigation of the specific heat cp of water-based Al2O3 nanofluid with a differential scanning calorimeter. The result indicates that the specific heat cp of nanofluid decreases gradually as the nanoparticle volume fraction ϕ increases from 0.0% to 21.7%. The relationship between them exhibits good agreement with the prediction from the thermal equilibrium model [Eq. (2)]. The other simple mixing model [Eq. (1)] fails to predict the specific heat cp of nanof… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

27
216
0
1

Year Published

2011
2011
2021
2021

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 541 publications
(244 citation statements)
references
References 42 publications
27
216
0
1
Order By: Relevance
“…For the specific heat experiments [20], a differential scanning calorimeter (DSC, Q20, TA, USA) at an accuracy of 1.0% with a mechanical cooling system (RCS40, TA, USA) measured the specific heat of Al 2 O 3 nanoparticle and nanofluid at 20-70 C. The sample was held in an aluminum sample pan (Tzero Pan, No. : T100915) with a lid (Tzero Hermetic Lid, No.…”
Section: Experimental Setup and Designmentioning
confidence: 99%
See 1 more Smart Citation
“…For the specific heat experiments [20], a differential scanning calorimeter (DSC, Q20, TA, USA) at an accuracy of 1.0% with a mechanical cooling system (RCS40, TA, USA) measured the specific heat of Al 2 O 3 nanoparticle and nanofluid at 20-70 C. The sample was held in an aluminum sample pan (Tzero Pan, No. : T100915) with a lid (Tzero Hermetic Lid, No.…”
Section: Experimental Setup and Designmentioning
confidence: 99%
“…Nanofluid is a solidliquid mixture, and therefore the concepts of mixing theory for ideal gas mixtures, and classical and statistical mechanism are useful to estimate the nanofluid density. The density of nanoparticles is usually greater than that of the bulk liquid; therefore, according to the concepts of mixing theory for ideal gas mixtures [14][15][16][17][18][19][20] and classical and statistical mechanisms [20][21][22][23][24][25][26][27][28][29], adding nanoparticles to the bulk liquid increases the density of the bulk liquid. Similarly, estimating the specific heat of nanofluid often requires the concepts of mixing theory for ideal gas mixtures and classical and statistical mechanism.…”
Section: Introductionmentioning
confidence: 99%
“…Determination of the effective specific heat of nanofluids is also important for their practical application in thermal system management. Research previously performed was limited to determining the specific heat of couple of nanofluids [9,10] Namburu et al [9] reported specific heat of nanofluids of silicon dioxide (20 nm) in solution of EG and water mixture. They observed a moderate decrease in specific heat of this nanofluid with increasing particle volume fraction.…”
Section: Introductionmentioning
confidence: 99%
“…The volume fraction mixture-based correlation underpredicts the measured results. Recently, Zhou and Ni [10] measured specific heat of Al 2 O 3 (45 nm)/water-based nanofluid by using a differential scanning calorimeter. Their results showed that the specific heat of this nanofluid decreases significantly with particle volume fraction.…”
Section: Introductionmentioning
confidence: 99%
“…The thermophysical properties of nanofluids (density, heat capacity, thermal conductivity and viscosity are calculated based on the correlations given in these References [33][34][35][36]. …”
Section: Grid Testing and Model Validationmentioning
confidence: 99%